STUDI KOMUNITAS GULMA DI AREAL PERTANAMAN PALA (Mirystica fragrans Houtt) PADA STADIUM TANAMAN BELUM MENGHASILKAN DAN MENGHASILKAN DI DESA RUTONG KECAMATAN LEITIMUR SELATAN KOTA AMBON - Anderson Onarely; Johan Riry; Anna Y Wattimena (Universitas Pattimura, 2016)
The research was conducted in Rutong Village, Ambon City in order to determine the composition of weeds and weeds as well as weeds predominant in the nutmeg crop yield and immature. Field data collection was done by using a survey method. The results showed the number of weeds in immature stages are found 21 species of weeds, while on the stage of the producing plant 22 types of weeds found. In stage producing plant, the dominant weed species was Selaginella willdenowii Backer with SDR 42.41%. On the immature stage, the dominant weed species were weeds Selaginella willdenowii Backer with SDR 34.38%. While the dominant weed was an annual broadleaf weed.